Sports analytics : a guide for coaches, managers, and other decision makers - Alamar, Ben (Columbia University Press, 2013)
"Benjamin C. Alamar founded the first journal dedicated to sports statistics, the Journal of Quantitative Analysis in Sports. He developed and teaches a class on sports analytics for managers at the University of San Fransisco and has published numerous cutting-edge studies on strategy and player evaluation. Today, he cochairs the sports-statistics section of the International Statistics Institute and consults with several professional teams and businesses in sports analytics. There isn't a better representative of this emerging field to show diverse organizations how to implement analytics in their decision-making strategies, especially as analytic tools grow increasingly complex. Alamar provides a clear, easily digestible survey of the practice and a detailed understanding of analyics' vast possibilities. He explains how to evaluate different programs and put them to use. Using concrete examples from professional sports teams and case studies demonstrating the use and value of analyitics in the field, Alamar designs a roadmap for managers, general managers, and other professionals as they build their own programs and teach their approach to others."--Inside Cover.